Executive equity incentive, supervisory board monitoring, religion and financial reporting quality in China - LI, HUIHUI (2018)
Informed by agency theory and stakeholder theory, this study examines the impact of corporate governance on financial reporting quality in the context of China mainly from three mechanisms such as equity incentive to executives, supervisory board monitoring and religion. Based on a sample of 280 Chinese listed companies over a ten-year period (2008-2017), this study finds that executives’ equity incentives increase their propensity to commit corporate fraud and destroys the financial reporting quality. However, in contrast to prior findings, supervisory board monitoring in China is effective. In particular, a smaller SB size can reduce earnings management, while SB meeting frequency does not have significant relation with earnings management. Lastly, this study reveals that religion (Buddhism and Taoism in this study) is significantly negatively associated with earnings management, suggesting that religion can serve as an informal mechanism to reduce earnings management and improve financial reporting quality.